2022
DOI: 10.3390/foods11142079
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis of the Fruit Pulp Extracts from Annona crassiflora Mart. and Evaluation of Their Antioxidant and Antiproliferative Activities

Abstract: Annona crassiflora Mart., the marolo fruit of the Cerrado biome, is one of the most frequently consumed species from the Brazilian Midwest. This study aimed to evaluate the chemical composition and the antioxidant and cytotoxic properties of the fruit pulp of A. crassiflora collected at Chapada das Mesas, Maranhão, Brazil. The volatile concentrate was identified as mainly ethyl octanoate, ethyl hexanoate, and methyl octanoate. From the ethanol (LFP-E) and ethyl acetate (LFP-A) extracts were identified phenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The stephalagine was purified by semi-preparative HPLC on RP-C 18 and structurally characterized by high-resolution mass spectrometry, with electrospray ionization (HR-ESI-MS) and nuclear magnetic resonance (NMR) techniques, for the first time by Pereira et al [ 29 ]. Additionally, recent studies have reported the presence of stephalagine in araticum peel and pulp [ 14 , 26 , 27 , 28 , 30 ], indicating that this compound is present in more than a fraction of the fruit. Stephalagine, an aporphine alkaloid, has demonstrated anti-obesity, antinociceptive, and anti-edematogenic effects, suggesting its use as a new potential drug [ 28 , 29 ].…”
Section: Bioactive Compounds Found In Araticum Fruit Partsmentioning
confidence: 99%
See 3 more Smart Citations
“…The stephalagine was purified by semi-preparative HPLC on RP-C 18 and structurally characterized by high-resolution mass spectrometry, with electrospray ionization (HR-ESI-MS) and nuclear magnetic resonance (NMR) techniques, for the first time by Pereira et al [ 29 ]. Additionally, recent studies have reported the presence of stephalagine in araticum peel and pulp [ 14 , 26 , 27 , 28 , 30 ], indicating that this compound is present in more than a fraction of the fruit. Stephalagine, an aporphine alkaloid, has demonstrated anti-obesity, antinociceptive, and anti-edematogenic effects, suggesting its use as a new potential drug [ 28 , 29 ].…”
Section: Bioactive Compounds Found In Araticum Fruit Partsmentioning
confidence: 99%
“…Stephalagine, an aporphine alkaloid, has demonstrated anti-obesity, antinociceptive, and anti-edematogenic effects, suggesting its use as a new potential drug [ 28 , 29 ]. In addition to stephalagine, other alkaloids, such as xylopine, romucosine, asimilobine, roemerine, nornuciferine, N -methylcoclaurine, guattescidine, actinodaphnine, isoboldine, and N -methyllaurotetanine, have been identified in araticum pulp [ 14 , 22 ]. Several studies demonstrated the presence of liriodenine, atherospermidine, isopiline, isoboldine, isocorydine, anonaine, xylopine, nuciferine, liriodenine, atherospermidine, reticuline, roemerine, nornuciferine, N -methylcoclaurine, guattescidine, actinodaphnine, and N -methyllaurotetanine in the araticum peel [ 22 , 26 , 30 ].…”
Section: Bioactive Compounds Found In Araticum Fruit Partsmentioning
confidence: 99%
See 2 more Smart Citations
“…The natural sources of oligomeric proanthocyanidins include the grape (seed and skin) [33,34], blueberry [35], Annona Crassiflora Mart. [36], coffee [37], polygonaceous plants [38], perennial ryegrass (Lolium perenne L.), and tall fescue (Festuca arundinace Schreb. [39] as shown in Table 1.…”
Section: Sources Of Oligomeric Proanthocyanidinsmentioning
confidence: 99%